ANALISIS PENGAMANAN DATA TELEMETRI DENGAN ALGORITMA RIJNDAEL DAN TWOFISH PADA SISTEM KOMUNIKASI SERIAL - I Dewa Gede Adhyatma Yasa Guang, - (2019)
Technology development, especially in the use of electronic devices, has now entered a new phase where tools start using telemetry with or without cables as a communication media, especially in robotics technology. One way of communication in robotics technology is serial data that uses computers as a medium to give commands to provide information needed to fulfill a need. From this interest, the serial data needs to be secured and based on the communication of giving orders to do something or get something certainly the media needed to be secured, namely Cryptography. Cryptography works by encoding messages or information sent and then neutralizes them back into information, with this system sending and receiving information can be secured from unwanted people. Cryptographic security which is now widely used, namely the algorithm Advanced Encryption Standard (AES) Rijndael and Twofish, and based on the need for security in communication, analyzing to find a good and appropriate algorithm is needed